2017
DOI: 10.3390/met7050179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep Cryogenic Treatment on the Microstructure and the Corrosion Resistance of AZ61 Magnesium Alloy Welded Joint

Abstract: Abstract:The effect of deep cryogenic treatment on the microstructure and corrosion resistance of an AZ61 magnesium alloy metal inert-gas (MIG) welded joint was investigated. The welded joints were deep-cryogenically treated using different parameters, and were analyzed by metallographic observations, X-ray diffraction, microhardness, and NaCl immersion test. The results show that the treatment changes the microstructure of the entire joint by causing grain refinement and increase in the β-phase. The crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Ramesh et al [24] measured an improvement of 69% in the corrosion resistance of rebar steel following DCT due to the increase of the perlite phase. Gong et al [25] improved the corrosion resistance to NaCl via an immersion test of AZ61 magnesium alloy welded joints after deep cryogenic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ramesh et al [24] measured an improvement of 69% in the corrosion resistance of rebar steel following DCT due to the increase of the perlite phase. Gong et al [25] improved the corrosion resistance to NaCl via an immersion test of AZ61 magnesium alloy welded joints after deep cryogenic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Deep Cryogenic Treatment (DCT) exerts a significant influence on both the grain morphology of welded joints and the precipitation of phases [27,28]. Given that these precipitates exert a strong impact on the properties of aluminum alloy, a variety of characterization methods, including SEM, XRD, EDS, and TEM, are employed to identify and distinguish these precipitates.…”
Section: Effect Of Dct On Precipitatesmentioning
confidence: 99%
“…The more refined α-grains and strengthening precipitates (Mg 17 Al 12 ) are the reasons for the higher hardness in the DCT as compared with the SCT. Gong et al [42] reported that the DCT improved the hardness in the fusion and HAZ regions of AZ61 Mg welded joints. Even though cryogenic treatment the HAZ region shows inferior hardness when compared to all the SZ regions and it may be due to the presence of eutectic phase.…”
Section: Microhardness Studies Of Fsw and Post Cryogenic Treated Jointsmentioning
confidence: 99%